Synthesis and absorption properties of acrylamide-grafted potato starch - Fomina, Elena K.; Klimovtsova, Iraida A.; Grinyuk, Evgeny V.; Lasminskaya, Marina V.; Kudryavsky, Dmitry L.; Fedorenko, Aleksandra A.; Shiman, Dmitri I.; Yakimenko, Oleg V. (Journal of the Belarusian State University. Chemistry, 2024)
Hybrid hydrogels were synthesised by grafting acrylamide onto the macromolecules of potato starch via radical mechanism in water-polymer systems. Ammonium persulfate was used as a polymerisation initiator, and N,N′-methylene-bis-acrylamide was used as a crosslinking agent. The structure and properties of acrylamide-grafted starch was studied by FTIR spectroscopy, X-ray diffraction and thermogravimetry. It is suggested that the primary carbon atoms of the polysaccharide are the main grafting centers of acrylamide onto starch macromolecules. The effect of reagents mass ratios on sorption and rheological properties of the obtained hydrogels was studied. Chemical modification of hydrogels based on acrylamide-grafted starch was carried out via alkaline hydrolysis, and its effect on the sorption capacity of the hydrogels towards heavy metal ions (Cu(II) ions as an example) was determined.
Keywords: potato starch; acrylamide; graft copolymers; sorption; Cu(II) ions